نظرية النسبية وملامح الفلسفة المعاصرة - سعيدي, عبد الفتاح (جامعة الوادي - University of Eloued, 2021)
يهدف البحث إلى طبيعة العلاقة بين الفلسفة المعاصرة من جهة والعلم المعاصر من جهة أخرى. ثم النظر، إن كان يجمعهما برديغم بحث موحد بينهما. وقع الاختيار على نظرية النسبية بصفتها أشهر نظرية علمية فيزيائية في القرن العشرين. توصلت في الأخير إلى أن أهم التصورات والمفاهيم التي قامت عليها النظرية النسبية هي نفسها أهم الملامح التي تميزت بها الفلسفة المعاصرة دون غيرها من الفلسفات. This research aims at the relationship between contemporary philosophy, on the one hand, and contemporary science on the other hand. And look, if it brings them together, despite unified search between them. I select the theory of relativity as the most famous scientific and physical theory of the 20the century. Ultimately, I concluded that the most important concepts on which the theory of relativity is based, are the same as the most important characteristics that characterize contemporary philosophy.
Relativistic theory and features of contemporary philosophy
مقال
Keywords: الفلسفة المعاصرة، نظرية النسبية، التأويل، الوعي، المراجع الفيزيائية; contemporary philosophy, the theory of relativity, interpretation , consciousness , physical referential .